Aggregation Induced Emission Fluorogens Based Nanotheranostics for Targeted and Imaging‐Guided Chemo‐Photothermal Combination Therapy. Issue 47 (24th August 2016) - Wang, Ke; Fan, Xingliang; Zhao, Lingyun; Zhang, Xiaoyong; Zhang, Xiqi; Li, Zhen; Yuan, Qian; Zhang, Qingsong; Huang, Zengfang; Xie, Wensheng; Zhang, Yuanyuan; Wei, Yen
Abstract : Nanotheranostics for biomedical imaging‐guided cancer therapy have attracted increasing interest due to their capabilities of both precise tumor diagnosis and high therapeutic efficacy. Among the diverse imaging models, fluorescence imaging have been extensively researched for their high sensitivity, simple operation, and low cost. In this work, aggregation induced emission (AIE) fluorogens based targeted nanotheranostics are facilely fabricated via paclitaxel (PTX) induced assembly of proteins for the first time. Thanks to the unique fluorescence property of AIE fluorogens PhENH2, the prepared theranostic nanoplatforms can emit bright fluorescence even after being incorporated with the photothermal therapy agent polypyrrole (PPy), which will often decrease or quench the emission of common fluorescence dyes. The target moiety of cyclic arginine–glycine–aspartic acid (cRGD) endows the nanotheranostics with outstanding targeting ability, which can further facilitate the targeted imaging and cancer treatment. As revealed by the in vitro and in vivo experiments, the prepared nanotheranostics human serum albumin‐PhENH2 ‐PPy‐PTX‐cRGD shows impressive performance in the targeted fluorescence imaging even after intravenous injection for 48 h, and their combined chemo‐photothermal therapy is also very effective. These results indicate that AIE fluorogens based nanotheranostics would find a promising prospect in further improved multimodal imaging and imaging guided cancer treatment. Abstract : Aggregation induced emission (AIE) fluorogens based targeted nanotheranostics are facilely fabricated through paclitaxel induced assembly of proteins for the first time, which demonstrates outstanding in vitro and in vivo targeted fluorescence imaging and imaging guided chemo‐photothermal combination therapy efficacy. These results indicate that AIE fluorogens based nanotheranostics will find a promising prospect in further improved multimodal imaging and cancer treatment.